Group Nutrition Counseling or Individualized Prescription for Women With Obesity? A Clinical Trial - Bolognese, Marciele Alves; Franco, Carina Bertoldi; Ferrari, Ariana; Bennemann, Rose Mari; Lopes, Solange Munhoz Arroyo; Bertolini, Sônia Maria Marques Gomes; Júnior, Nelson Nardo; Branco, Braulio Henrique Magnani (Frontiers in Public Health, 2020)
Background: This study investigates the effects of group counseling versus individual dietary prescription on physical, nutritional, and mental health in overweight or obese women. Methods: Seventy-four women aged 40-59 years with body mass index ≥ 25 kg/m2 were randomized into 2 intervention arms: group nutrition counseling (GNC) or individualized nutrition prescription (INP). Twenty-seven women completed the 12-week intervention protocol. The GNC received counseling once a week and the INP received an individualized prescription once a month. All participants attended physical exercise sessions 3 times a week following the same protocol. Body mass, body mass index, fat mass, body fat percentage, lean mass, lipid profile, hemoglobin A1c, insulin and liver transaminases were measured pre- and post-intervention in both arms. A three-day food record was applied to calculate the intake of calories, carbohydrates, proteins, and lipids. Body image dissatisfaction, level of anxiety, self-esteem measure and pathological eating attitudes were measured. Results: Both dietary interventions decreased body mass, body mass index, fat mass, body fat percentage, total caloric intake, carbohydrates, proteins, lipids, body dissatisfaction, anxiety, and saturated and polyunsaturated fats (p<0.05). Lean mass, metabolic variables, self-esteem and pathological eating attitudes remained unchanged (p>0.05). Conclusion: Both nutritional interventions combined with concurrent exercise were effective to improve anthropometrics, body composition, food intake, and some mental health parameters. We suggest that the choice of nutritional intervention (GNC or INP) could be based on the participants preference, considering the adherence and satisfaction, to promote health and quality of life.